Pyramiding of Fusarium Head Blight Resistance Quantitative Trait Loci, Fhb1, Fhb4, and Fhb5, in Modern Chinese Wheat Cultivars - Zhang, Yiduo; Yang, Zibo; Ma, Haicai; Huang, Liying; Ding, Feng; Du, Yingying; Jia, Haiyan; Li, Guoqiang; Kong, Zhongxin; Ran, Congfu; Gu, Zhengzhong; Ma, Zhengqiang (Frontiers in Plant Science, 2021)
Wheat production is increasingly threatened by the fungal disease Fusarium head blight (FHB) caused by Fusarium spp. Introduction of resistant varieties is considered to be an effective measure for containment of this disease. Mapping of FHB-resistant QTL has promoted marker-assisted breeding for FHB resistance, which has been difficult through traditional breeding due to paucity of resistance genes and quantitative nature of the resistance. Ma's lab previously cloned Fhb1 that inhibits FHB spread within spikes and fine mapped Fhb4 and Fhb5 that condition resistance to initial infection of Fusarium spp, from FHB-resistant indigenous line Wangshuibai. In this study, these three QTL were simultaneously introduced into five modern Chinese wheat cultivars or lines with different ecological adaptations through marker-assisted backcross in early generations. A total of 14 introgression lines were obtained. All these lines showed significantly improved resistance to the fungal infection and disease spread in two-year field trials after artificial inoculation. In comparison with the respective recipient lines, the Fhb1, Fhb4 and Fhb5 pyramiding could reduce the disease severity by 95% and did not systematically affect plant height, productive tiller number, kernel number per spike, thousand grain weight and flowering time, as well as unit yield (without Fusarium inoculation). These results indicated the great value of FHB-resistant QTL Fhb1, Fhb4 and Fhb5 derived from Wangshuibai, and feasibility and effectiveness of early-generation for FHB resistance solely based on linked molecular markers.